2013
DOI: 10.1161/hyp.62.suppl_1.a233
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 233: Resistance Training Attenuates Renal Dysfunction in Animal Diabetic Nephropathy but Does Not Restore Kidney ACE/ACE2 Balance

Abstract: Overactivity of the intrarenal renin-angiotensin system (RAS) has been implicated in the pathogenesis of diabetic nephropathy. Our group has already demonstrated that aerobic exercise reduces kidney angiotensin II levels and attenuates renal dysfunction under concurrence of diabetes and hypertension. Resistance training (RT) has recently been recognized as a useful therapeutic tool for the treatment chronic diseases and similar to aerobic exercise, has been reported to improve glycemic control. Therefore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Accordingly, by a simple analogy between the results of the CG and RTG, it can be logically concluded that RT, though it did not improve kidney function, at least stopped the development of kidney dysfunction and prevented eGFR from decreasing in the RTG, whereas the kidney function of the CG probably deteriorated due to the lack of RT, resulting in the increased levels of IGFBP-3. This justification can be supported by the report of Santos et al who showed that RT could attenuate renal dysfunction in animal DN after an 8-week training period (31). However, it seems that the improvement of kidney function relies on various sophisticated physiological adaptations, requiring the long-term intervention of proper exercise therapy; otherwise, significant improvement can be barely observed through short-term training programs.…”
Section: Discussionmentioning
confidence: 88%
“…Accordingly, by a simple analogy between the results of the CG and RTG, it can be logically concluded that RT, though it did not improve kidney function, at least stopped the development of kidney dysfunction and prevented eGFR from decreasing in the RTG, whereas the kidney function of the CG probably deteriorated due to the lack of RT, resulting in the increased levels of IGFBP-3. This justification can be supported by the report of Santos et al who showed that RT could attenuate renal dysfunction in animal DN after an 8-week training period (31). However, it seems that the improvement of kidney function relies on various sophisticated physiological adaptations, requiring the long-term intervention of proper exercise therapy; otherwise, significant improvement can be barely observed through short-term training programs.…”
Section: Discussionmentioning
confidence: 88%